2015
DOI: 10.1021/acs.macromol.5b00439
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Functional Polypropylene Containing Hindered Phenol Stabilizers and Applications in Metallized Polymer Film Capacitors

Abstract: This paper discusses a new family of polymeric stabilizers (antioxidants) containing a polypropylene backbone and several pendant hindered phenol groups (PP-HP), with both random and tapered copolymer microstructures. They are effectively prepared by Steglich esterification of the corresponding hydroxylated polypropylene (PP-OH) copolymers with the hindered phenol molecule containing a carboxylic acid moiety. Some resulting PP-HP copolymers show significantly higher thermal-oxidative stability than the pristin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 51 publications
0
62
0
Order By: Relevance
“…HCl and extracted with 30 ml of DCM. The organic layer was extracted by saturated naHCO 3 solution and dried over na 2 SO 4 followed by evaporation of extra solvent under reduced pressure. The chemical structures of synthesized antioxidants along with 13 C nMR spectra are shown in Figures 1 and 2 proved the potential antioxidant ability and revealed that polarity and hydrophobicity of stabilizers can be determining factors in efficiency of antioxidants.…”
Section: Synthesis Of Esters Of 35-di-tert-butyl-4-hydroxybenzoic Acmentioning
confidence: 99%
See 3 more Smart Citations
“…HCl and extracted with 30 ml of DCM. The organic layer was extracted by saturated naHCO 3 solution and dried over na 2 SO 4 followed by evaporation of extra solvent under reduced pressure. The chemical structures of synthesized antioxidants along with 13 C nMR spectra are shown in Figures 1 and 2 proved the potential antioxidant ability and revealed that polarity and hydrophobicity of stabilizers can be determining factors in efficiency of antioxidants.…”
Section: Synthesis Of Esters Of 35-di-tert-butyl-4-hydroxybenzoic Acmentioning
confidence: 99%
“…[1][2][3] Also, radicals and active oxygens from materials which are in direct contact with foods can be responsible for severe diseases or even cancer. [4] To address the issue, it has been suggested to add sufficient amounts of stabilizers based on material type to inhibit degradation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyethylene and polypropylene are the polyolefin resins with the largest commercial scale. It follows then that most researches on the synthesis of the functional polyolefin concern ethylene [4][5][6][7][8][9][10][11][12][13] and propylene [14][15][16][17][18] copolymerization. The investigation on the copolymerization of higher α-olefin with functional monomer was rather rare.…”
Section: Introductionmentioning
confidence: 99%